Cardiac injury progression in children with multisystem inflammatory syndrome associated with SARS-CoV-2 infection: a review - Su, Song; Hu, Wandong; Chen, Xiao; Ren, Ying; Lu, Yi; Shi, Jianguo; Zhang, Tong; Zhang, Huan; Wang, Meng; Wang, Yaping; Zhao, Fen; Jin, Ruifeng; et al. (Frontiers in Pediatrics, 2024)
The symptoms and signs of infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are milder in children than in adults. However, in April 2020, British pediatricians first reported that coronavirus disease 2019 (COVID-19) may present as multisystem inflammatory syndrome in children and adolescents (MIS-C), similar to that observed in Kawasaki disease. MIS-C can be associated with multiple systemic injuries and even death in children. In addition to digestive system involvement, cardiac injury is prominent. This article reviews the pathogenesis, clinical manifestations, and treatment of cardiac injury caused by MIS-C, which may help clinicians in early diagnosis and timely commencement of treatment.